Pengaruh lingkungan kerja dan kepemimpinan terhadap produktivitas kerja melalui kepuasan kerja pegawai pada sekretariat daerah kabupaten pangkep - Ismail Haeruddin; Muhammad Idris; Sylvia Sjarlis (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat ITB Nobel Indonesia, 2021)
Ismail Haeruddin. 2020. The Effect of Work Environment and Leadership on Employee Productivity through Job Satisfaction at the Regional Secretariat of Pangkep Regency) (supervised by Muhammad Idris and Sylfia Sjarlis) The research aims to analyze: 1) the direct influence of the work environment and leadership on employee job satisfaction at the Regional Secretariat of Pangkep Regency, 2) the direct influence of the work environment and leadership on the work productivity of employees at the Regional Secretariat of Pangkep Regency, and 3) the indirect influence of the work environment and leadership on employee work productivity through job satisfaction at the Regional Secretariat of Pangkep Regency. This research design using survey research. This research will be carried out at the Regional Secretariat of Pangkep Regency from October to November 2019. The population in the study was all employees at the Regional Secretariat of Pangkep Regency totaling 103 people who were provided as samples. The data analysis technique uses path analysis. The results showed that: 1) there was a positive and significant effect directly on the work environment and leadership on employee job satisfaction at the Regional Secretariat of Pangkep Regency, 2) there was a positive and significant effect directly on the work environment and leadership on employee work productivity at the Regional Secretariat of Pangkep Regency. , and 3) there is a positive and indirect effect of the work environment and leadership on employee work productivity through job satisfaction at the Regional Secretariat of Pangkep Regency. Keywords: environment, leadership, satisfaction and productivity